N6-Methyladenosine Inhibits Local Ribonucleolytic Cleavage to Stabilize mRNAs in Arabidopsis - Fray, Rupert G (Elsevier, 2018)
N6-methyladenosine (m6A) is a dynamic, reversible, covalently modified ribonucleotide that occurs predominantly toward 30 ends of eukaryotic mRNAs and is essential for their proper function and regulation. In Arabidopsis thaliana, many RNAs contain at least one m6A site, yet the transcriptome-wide function of m6A remains mostly unknown. Here, we show that manym6A-modified mRNAs in Arabidopsis have reduced abundance in the absence of this mark. The decrease in abundance is due to transcript destabilization caused by cleavage occurring 4 or 5 nt directly upstream of unmodified m6A sites. Importantly, we also find that, upon agriculturally relevant salt treatment, m6A is dynamically deposited on and stabilizes transcripts encoding proteins required for salt and osmotic stress response. Overall, our findings reveal that m6A generally acts as a stabilizing mark through inhibition of site-specific cleavage in plant transcriptomes, and this mechanism is required for proper regulation of the salt-stress-responsive transcriptome.